Modified Cervicofacial Rotation Flap with Tissue Expansion for Cosmetic Resection of a Large Hemifacial Congenital Nevus. (23rd August 2013) - Miguel, George S.; Standring, Robert T.; Darian, Vigen; Schweitzer, Vanessa G.
Abstract : Objectives: A 23‐year‐old Armenian female was evaluated in Armenia by the senior author and sponsoring church members for a deforming 8.5 × 6 cm heavily pigmented congenital nevus involving the right hemiface (cheek, eyelids, nose). The lesion affected function of the right lower eyelid. The patient wore her hair long with bangs as a camouflaging mask to wrap around her face. Methods: She was shortly thereafter brought to the United States for cosmetic reconstructive surgery for this lesion. She underwent a 2‐stage procedure: tissue expander placement with full thickness skin graft of the right lower eyelid defect, with subsequent removal of the expander two months later and modified cervicofacial angle rotation flap with full thickness skin graft to the nasal bridge, creating a superb cosmetic closure. Conclusions: Intra‐operative photographs detail the 2‐staged angle rotation flap reconstruction.